2009
DOI: 10.1186/bcr2457
|View full text |Cite
|
Sign up to set email alerts
|

Human mammary cancer progression model recapitulates methylation events associated with breast premalignancy

Abstract: IntroductionWe have previously identified a rare subpopulation of variant human mammary epithelial cells (vHMEC) with repressed p16INK4A that exist in disease-free women yet display premalignant properties, suggesting that they have engaged the process of malignant transformation. In order to gain insight into the molecular alterations required for vHMEC to progress to malignancy, and to characterize the epigenetic events associated with early progression, we examined the effect of oncogenic stress on the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…These changes may be partially explained by alterations in the expression of genes critical for mammary gland development and by an increase in the number of mammosphere forming cells. Previously, it has been demonstrated that suppression of SFRP1 expression is an early change in human premalignant breast lesions [21]. Taken together, our study indicates that the SFRP1 gene is critical for maintaining proper mammary gland development, that reduced levels of SFRP1 results in hyperplastic lesions, and its loss may be a critical event in cancer initiation.…”
Section: Discussionsupporting
confidence: 71%
“…These changes may be partially explained by alterations in the expression of genes critical for mammary gland development and by an increase in the number of mammosphere forming cells. Previously, it has been demonstrated that suppression of SFRP1 expression is an early change in human premalignant breast lesions [21]. Taken together, our study indicates that the SFRP1 gene is critical for maintaining proper mammary gland development, that reduced levels of SFRP1 results in hyperplastic lesions, and its loss may be a critical event in cancer initiation.…”
Section: Discussionsupporting
confidence: 71%
“…Previously, it has been demonstrated that suppression of SFRP1 expression is an early change in human premalignant breast lesions [58] and loss of Sfrp1 in the mouse mammary gland results in hyperplastic lesions [36]. In this study we clearly demonstrate that the mammary glands of Sfrp1 -/- mice exhibit enhanced macrophage infiltration (Figure 5A;Figure S5).…”
Section: Discussionsupporting
confidence: 71%
“…Suppression of SFRP1 expression is also linked to early changes in human premalignant breast lesions (Dumont et al, 2009), and may represent a novel diagnostic marker in women thought to have atypical ductal hyperplasia and/or lobular carcinoma in situ. Nonetheless, whether SFRP1 loss is merely associated with breast cancer development or definitively leads to breast cancer development is unclear.…”
Section: Discussionmentioning
confidence: 99%